3x+6=cox+d

Simple and best practice solution for 3x+6=cox+d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6=cox+d equation:


Simplifying
3x + 6 = cox + d

Reorder the terms:
6 + 3x = cox + d

Solving
6 + 3x = cox + d

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1cox' to each side of the equation.
6 + -1cox + 3x = cox + -1cox + d

Combine like terms: cox + -1cox = 0
6 + -1cox + 3x = 0 + d
6 + -1cox + 3x = d

Add '-6' to each side of the equation.
6 + -1cox + -6 + 3x = -6 + d

Reorder the terms:
6 + -6 + -1cox + 3x = -6 + d

Combine like terms: 6 + -6 = 0
0 + -1cox + 3x = -6 + d
-1cox + 3x = -6 + d

Reorder the terms:
6 + -1cox + -1d + 3x = -6 + d + 6 + -1d

Reorder the terms:
6 + -1cox + -1d + 3x = -6 + 6 + d + -1d

Combine like terms: -6 + 6 = 0
6 + -1cox + -1d + 3x = 0 + d + -1d
6 + -1cox + -1d + 3x = d + -1d

Combine like terms: d + -1d = 0
6 + -1cox + -1d + 3x = 0

The solution to this equation could not be determined.

See similar equations:

| (X-3)(3x+6)= | | N^2=12+4n | | 49/100x^2=0 | | 4W+5M=2700 | | 16w^2+40w-24=0 | | 8/21=2/7x | | 32x+7x-38x=50 | | y=(x-2)(x-4) | | f=-0.8+0.6x | | 6sin^2x+12sinx+6=0 | | 10x+6x=1 | | 6log(25-x^2)-(log(5+x)+log(5-x))=x | | -2(x-6)=-5(x-1) | | (3/(2sqrtx))-1 | | 36=1/25x^2 | | 6a^4b^4-2a^3b+8a^2= | | x^2+16x-360=0 | | 0.22*f=13.2 | | 1/4x^3=2 | | 8-3b=11-2b | | 72x+28x-99x=-50 | | 7b=2 | | 0=9(k-.667)+33 | | Y=3.5x-7 | | 5y=8x-80 | | 8x^6-32x^5+4x^4= | | f(-5)=-3x+4 | | 3/p-5=-14 | | 5(13+k)= | | (10a+4)= | | 2x+3x*y=3 | | 5.54x+100=30.6916+10x |

Equations solver categories